The Conception of the Individual in Non-Cooperative Game Theory - John B. Davis (Tinbergen Institute, 2003)
This paper examines the conception of individuals as being of certain types in Harsanyi'stransformation of games of incomplete information into games of complete information. Itargues that while the conception of the individual in games of complete information offerspotential advances over the problematic neoclassical conception of the individual, Harsanyi'smore realistic incomplete information games framework essentially re-introduces the difficultiesfrom the neoclassical conception. A further argument of the paper is that flxed point equilibriumexistence proof theorems and individual existence proofs function in an analogous manner, andcan consequently been seen as both dependent upon one another. Thus the inadequacy ofHarsanyi's conception of individuals raises questions about Nash equilibrium approaches toequilibria in games.
Keywords: C7; D5; 330; conceptions of individuals; Harsanyi; games of incomplete information; fixed point theorems; Nash equilibrium; Nichtkooperatives Spiel